(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Anthropometric characteristics have a direct relationship with sex, shape and form of an individual, and these factors are closely linked with each other in estimating the height of an individual from the available data, which forms the basis of forensic anthropology. The objective of this study was to formulate a regression equation to estimate the height of an individual by using percutaneous measurement of the radial and ulnar bone lengths in the Gujarati population. A cross-sectional survey was conducted at a teaching hospital in Vadodara, Gujarat, India. A total of 110 Gujarati students aged above 20 years were enrolled for the study. The standing height and percutaneous length of the radial and ulnar bones of both the sides were measured and recorded. Stature estimation can be done successfully for both males and females by using the different regression equations obtained in this study, of which the left radius is specific for males and the left ulna for females. This study will be of great help for the forensic experts, the anthropologists and the anatomists in solving various medico-legal issues.